Avian diversity and conservation value in Tram Chim Ramsar site, Mekong Delta, Vietnam - LE DIEM KIEU; LE NHAT BAN; PHAM QUOC NGUYEN (Society for Indonesian Biodiversity, 2026)
Abstract. Kieu LD, Ban LN, Nguyen PQ. 2026. Avian diversity and conservation value in Tram Chim Ramsar site, Mekong Delta, Vietnam. Biodiversitas 27 (5): d270504. https://doi.org/10.13057/biodiv/d270504. Tram Chim National Park is a Ramsar site in the Mekong Delta, Vietnam, which is important for the conservation of bird species in Vietnam and migratory species worldwide. This study assessed the biodiversity, conservation value, and population structure of birds in the Tram Chim National Park Ramsar site using direct observation of 23 transects, conducted monthly throughout 2022. The survey recorded 139 bird species across 49 families and 17 orders. The bird community showed high biodiversity and uniformity, which was relatively stable between the dry and rainy seasons (p>0.05), with d, H’ and J’ values 8.14-11.97, 2.24-3.38 and 0.52-0.75, respectively. However, the biodiversity of the bird community continued to decline significantly in both richness and uniformity during the transitional months (June, July, November and December). The presence of numerous migratory and endangered bird species, as listed in the IUCN, CITES, and the Vietnam Red Book, confirms that the Tram Chim Ramsar Site is a crucial link in the global conservation of bird species. The structure of migratory birds, forest/water birds, and feeding groups fluctuated seasonally. The results of this study suggest that maintaining biodiversity resilience requires appropriate hydrological management informed by seasonal ecological information, ensuring the long-term conservation function of the global bird migration network.